Being Arab - Kassir, Samir 1960-2005 (Verso, 2013)
"Before his assassination in 2005, Samir Kassir was one of Lebanon's foremost public intellectuals. In 'Being Arab', a thought-provoking assessment of Arab identity, he calls on the people of the Middle East to reject both Western double standards and Islamism in order to take the future into their own hands. Passionately written and brilliantly argued, this rallying cry for change has now been heard by millions."--p.[4] of cover